Identifikasi Bacillus thuringiensis Dari Tanah Kebun Kelapa Sawit Kabupaten Batubara Menggunakan Pewarnaan Coomassie Brilliant Blue (CBB) - Siregar, Roza Ulfayanti; Suryanto, Dwi; Tanjung, Masitta (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to simply identify Bacillus thuringiensis isolates from oil palm plantation soil in Batubara Regency through Coomassie Brilliant Blue (CBB) staining. Soil samples were isolated using a serial dilution method and then grown on selective media. The colonies formed were observed based on the morphological characteristics of Bt. The results of this study indicate that several isolates have morphological characteristics that match the characteristics of Bacillus thuringiensis. CBB staining successfully detected the presence of crystalline proteins in several isolates, characterized by the formation of crystals and the ability to bind blue dye in cells that have undergone sporulation, indicating the presence of delta-endotoxin. This study confirms that oil palm plantation soil in Batubara Regency has the potential as a source of local Bt isolates. The Bt isolates found can be used as initial candidates in the development of biopesticides while supporting environmentally friendly and sustainable pest control strategies.